2023
DOI: 10.5603/fm.a2022.0085
|View full text |Cite
|
Sign up to set email alerts
|

An aberrant right subclavian artery in a 63-year-old male cadaver

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Folia Morphologica" are listed in PubMed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In the case described, the right vertebral artery was not a branch of the right subclavian artery, but arose as a branch of the right common carotid artery. The ARSA left the thoracic cage through the upper thoracic orifice [18]. This departure of the right vertebral artery is not the rule, when ARSA is present, however, as Ito et al describing two cases of ARSA on cadavers found vertebral arteries departing from the subclavian arteries in both cases [19].…”
Section: Anatomymentioning
confidence: 97%
See 1 more Smart Citation
“…In the case described, the right vertebral artery was not a branch of the right subclavian artery, but arose as a branch of the right common carotid artery. The ARSA left the thoracic cage through the upper thoracic orifice [18]. This departure of the right vertebral artery is not the rule, when ARSA is present, however, as Ito et al describing two cases of ARSA on cadavers found vertebral arteries departing from the subclavian arteries in both cases [19].…”
Section: Anatomymentioning
confidence: 97%
“…At its origin, the diameter of the ARSA was 12.9 cm, at the intersection of the esophagus and trachea it was 9.9 cm, and after the costocervical trunk it was 8.4 cm. The left subclavian artery in its origin had a diameter of 8.3 cm [18].…”
Section: Anatomymentioning
confidence: 99%